A juridical-canonical perspective of internal criticism in the Church: Act of service or treason? - Juan María Martínez Otero (Church, Communication and Culture, 2022)
In the last decade, we have witnessed a progressive increase in criticism of the Pope, the hierarchy, and the Roman Curia from within the Church itself. In this context of growing contestation and polarization, this paper addresses the legal-canonical admissibility of internal criticisms of the Church hierarchy. To this end, after first delimiting the concepts of criticism and hierarchy, the normative framework applicable to criticism is then described. This framework is essentially composed of canon 212 § 3 (which recognizes freedom of expression) and the canons 209 § 1, 212 § 1 and 223 § 1 (which establish the duties of communion and obedience). Then, the opportunities and dangers of internal criticism in the Church are analyzed. Finally, a series of criteria that may be useful for discerning the lawfulness of internal criticism in the Church is presented.